What happens to diet quality in people newly diagnosed with type 2 diabetes? The 3D case‐series study. Issue 1 (25th October 2021) - Burch, Emily; Williams, Lauren T.; Thalib, Lukman; Ball, Lauren
Abstract: Background: Diet quality plays an important role in the prevention of diabetes‐related complications in people with type 2 diabetes mellitus (T2DM). However, evidence is scarce on how diet quality typically changes over time after diagnosis. The present study aimed to describe how the diet quality of individuals newly diagnosed with T2DM changes over a 12‐month period and to identify factors associated with diet quality changes. Methods: A 12‐month prospective, observational case‐series study was undertaken. Two‐hundred and twenty‐five Australian adults (56% men) newly diagnosed with T2DM were recruited from the Diabetes Australia national database. Participants completed five interviewer‐administered surveys over 12 months: baseline, 3, 6, 9 and 12 months. Demographic, physical and health characteristics, and dietary intake data were collected at each timepoint. Diet quality was assessed using the Dietary Approaches to Stop Hypertension (DASH) scoring tool. To assess changes in DASH, energy, fruit and vegetable intake over time, repeated measure analyses of variance were used. Multivariate repeated measures models investigated characteristics associated with these dietary changes. Results: The mean DASH score of the sample remained stable at 24.0 across the 12 months. Very few participants (6.8%) improved diet quality consistently across the study period. No associations between DASH, energy, fruit or vegetable intake over time and characteristics were observed. Conclusions: This observational study suggests that without dedicated interventions (the natural course), most people newly diagnosed with T2DM will not achieve meaningful diet quality change. The development of cost‐effective interventions to achieve sustained diet quality change early after diagnosis are warranted. Abstract : Key points: Having a high diet quality is integral for the prevention of diabetes‐related complications in people with type 2 diabetes (T2DM). However, it is unclear how the diet quality of this group changes over time after diagnosis. The 3D case‐series study aimed to describe how the diet quality of 225 individuals newly diagnosed with T2DM changes over a 12‐month period and to identify factors associated with such change. The diet quality of the sample remained stable across the study period, with very few (6.8%) participants consistently improving. No associations with diet quality, energy, fruit or vegetable intake over time and demographic, physical or psychosocial characteristics were observed. Without dedicated interventions, most people with T2DM are unlikely to achieve meaningful dietary change.